2007
DOI: 10.1249/01.mss.0000239398.78331.96
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Running Training on DMH-Induced Aberrant Crypt Foci in Rat Colon

Abstract: The results of the present investigation suggest that low-intensity running training inhibits the DMH-induced initiation of colon ACF development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
3
11
0
1
Order By: Relevance
“…The mostly used carcinogen for inducing colon cancer in the animal model is azoxymethane (AOM), the metabolite of dimethylhydrazine (DMH) but more toxic than DMH. It was found that the injection of 20 mg/kg wt of DMH for 5 weeks resulted in 28–30 ACFs [18, 19]. The injection of AOM in similar dosages produced much more severe symptoms, in which more than 200 ACFs were induced [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…The mostly used carcinogen for inducing colon cancer in the animal model is azoxymethane (AOM), the metabolite of dimethylhydrazine (DMH) but more toxic than DMH. It was found that the injection of 20 mg/kg wt of DMH for 5 weeks resulted in 28–30 ACFs [18, 19]. The injection of AOM in similar dosages produced much more severe symptoms, in which more than 200 ACFs were induced [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, epidemiologic evidence indicates a negative correlation between exercise amount and subsequent risk of developing colorectal cancer (5,24,34,42). In experimental studies, a treadmill running exercise reduced the number of 1,2-dimethylhydrazine-induced aberrant crypt foci, a biomarker for colorectal carcinogenesis, in rats (14). In Apc min mice, voluntary (20) and treadmill (4) running exercise inhibited intestinal tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, a mild aerobic training counteracted the effects of carcinogen exposure, reducing proliferation and inflammation in the colon (3). Aerobic training has also been shown to reduce not only preneoplastic lesion, but also tumor formation in the colon (4,5). Our results, together with those of previous studies (3-5, 17, 32), highlight that physical exercise has different effects depending on its modality and the tissue analyzed, as well as on carcinogen exposure.…”
Section: Discussionsupporting
confidence: 79%